Gastrointestinal angiodysplasia is associated with significant gastrointestinal bleeding in patients with continuous left ventricular assist devices - Cochrane, Justin; Jackson, Christian; Schlepp, Greg; Strong, Richard (Endoscopy International Open, 2016)
Background and study aims: Patients with a continuous-flow left ventricular assist device (LVAD) have a 65 % incidence of bleeding events within the first year. The majority of gastrointestinal bleeding (GIB) is from gastrointestinal angiodyplasia (GIAD). The primary aim of the study was to determine whether GIAD was associated with a higher rate of significant bleeding, an increased number of bleeding events per year, and a higher rate of transfusion compared to non-GIAD sources. Patients and methods: This retrospective cohort study included 118 individuals who received a LVAD at a tertiary medical center from 2006 through 2014. Patients were subdivided into GIB and non-GIB for comparison of patient demographics, comorbid conditions, and laboratory data. GIB was further divided into sources of GIB, GIAD, obscure, or non-GIAD to establish severity of bleeding, rate of re-bleeding, and transfusion rate.Results: GIAD is associated with an increased number of bleeding events compared to non-GIAD sources of GIB (2.07 vs 1.23, P = 0.01) and a higher number of bleeding events per year (0.806 vs. 0.455 P = 0.001). GIAD compared to non-GIAD sources of GIB was associated with an increased incidence of major bleeding (100 % vs 60 %, P = 0.006) and increased rates of transfusion (8.8 vs 2.95 units, P = 0.0004). Cox Regression analysis between non-GIB and GIAD demonstrated increased risk with age (P = 0.001), history of chronic kidney disease (P = 0.005), and length of stay after LVAD implantation of more than 45 days (P = 0.04). History of hypertension (P = 0.045), diabetes mellitus (P = 0.016), and male gender was associated with decreased risk (P = 0.04). Conclusion: Patients with a continuous-flow LVAD who develop a GIB secondary to GIAD have a higher rate of major bleeding, multiple bleeding events, and require more transfusions to achieve stabilization compared to patients who do not have GIAD.